Financial Integration in Emerging Asia: Challenges and Prospects - Cyn-Young Park; Jong-Wha Lee (Asian Development Bank (ADB), 2011)
Using both quantity- and price-based measures of financial integration, this paper shows an increasing degree of financial openness and integration in emerging Asian markets. This paper also assesses the impact of a regional shock relative to a global shock on local equity and bond markets. The findings of this paper suggest that the region's equity markets are integrated more globally than regionally, although the degrees of both regional and global integration have increased significantly since the 1997/98 Asian financial crisis. However, emerging Asia's local currency bond markets remain generally segmented, being neither regionally nor globally integrated. A case can be made for the benefits of increased regional integration of financial markets. Financial integration at the regional level allows for the region's economies to benefit from allocation efficiency and risk diversification. The findings of this paper suggest that policymakers in the region must strike the right balance between maximizing the net benefits from regional and global financial openness, and minimizing the potential costs of financial contagion and crisis.
hdl:11540/2031
Keywords: F30; F36; F41; G15; 330; emerging Asia; financial integration; cross-border financial flows; crossborder asset holdings; convergence of asset returns